Effectiveness of HRM Practices in Creating Job Satisfaction of Ukrainian Employees Working in Poland - Gadomska-Lila, Katarzyna; Sudolska, Agata; Moskalenko (Rymarenko), Victoria (My University, 2020)
The aim of the study to explore the relationship between HRM practices and job satisfaction of Ukrainian employees working in Poland. Design/Methodology/Approach: This paper applies a quantitative methodology. The study is based on questionnaires conducted in Ukraine and filled in by 441 people who had worked and continue work in Poland. Findings: The results demonstrate that there is a significant relationship between HRM practices, particularly around compensation and reward, applied in the case of employees from Ukraine, and their job satisfaction. Practical Implications: The findings of this research are beneficial for HRM managers in Polish enterprises who hire employees from Ukraine and would like to satisfy them and retain them longer, as they confirm the importance of certain practices and facilitate their efficient selection. Originality/Value: This research is valuable in terms of recognizing the relationship between the use of certain Human Resources Management practices in Polish enterprises and Ukrainian employees job satisfaction.
Keywords: Human Resources Management practices; Ukrainian employees; job satisfaction; практика управління людськими ресурсами; українські працівники; задоволеність роботою; кафедра економіки праці та менеджменту